Histopathological findings of prostatic autopsy in a sample of over 50 years old men in Baghdad, Iraq - Abid, Ali Hussein; Mohammad, Ehab Jasim; Abdulrazaq, Alaa Abdulqader (International Surgery Journal, 2017)
Background: Incidental carcinoma of the prostate is very important is one of the major life-threatening condition for men at all ages. The incidence was found to increase with age. The aim of this study was to evaluate prostatic autopsy samples from Iraqi men over 50 years of age. Methods: 100 autopsy samples of whole prostate were collected from the Institute of Forensic Medicine in Baghdad. All the autopsy cases over 50 years of age died from causes unrelated to prostatic disease. Results: Age ranges from 50-80 years and the mean age was 59.3 years. Benign prostatic hyperplasia was the common pathological finding (92%). Forty-eight cases of benign prostatic hyperplasia were associated with chronic non-specific prostatitis (CNP), 6 cases were associated with low grade prostatic intraepithelial neoplasia and 2 cases with infarction and 6 cases of low grade prostatic intraepithelial neoplasia. Prostatic adenocarcinoma was detected in 6% of the cases. The mean weight was 39.9gm. The mean ellipsoid volume was 34.9cm3. The mean spheroid volume was 36.1cm3. The majority of benign prostatic hyperplasia cases were found in the 6th decade. Conclusions: From the present study, we can conclude that the majority of cases were in the 6th decade, benign prostatic hyperplasia was the most common finding, the most common association with benign prostatic hyperplasia was chronic nonspecific prostatitis, a low frequency of prostatic carcinoma and it was not associated with benign prostatic hyperplasia.